Surveillance of University Soccer Team Injuries over Two Years - Hirano, Y; Seto, H; Izumi, S (Japanese Journal of Clinical Sports Medicine, 2023)
The purpose of the present study was to assess the surveillance of male collegiate soccer team injuries for two years based on the FIFA definitions.Two-year injury surveillance was conducted on teams belonging to the Kanto Collegiate Soccer League using the method recommended by FIFA to investigate (1) the number of injuries, (2) injury rate, (3) injury burden, (4) site of injury, and the risk matrix for each injury site.The injury rate in this study was 3.45 [2.88-4.02]/1000 ph, which is lower than the J-League and European professional categories, but the injury burden was 79.85 [78.28-83.58]/1000 ph, which is comparable to European professional teams. This is because the subjects have fewer games per year and a lower level of competition, resulting in a lower incidence rate, but injuries are more likely to be severe because medical resources and funding are less than those of professional teams.In this study, the ankle joint was the most common injury site, and this result is similar to those of several previous studies of Japanese university soccer teams and may be a common problem in this category.